Penguatan Kapasitas Usaha Mikro Kecil dan Menengah Bengkel Otomotif melalui Pelatihan Sistem Starter Berbasis Mikrokontroler - Dwi Jatmoko; Widiyatmoko Widiyatmoko; Muhammad Rizky Fadilah; Piyan Prasetiawan; Bekti Wulandari; Hamid Nasrullah (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
This community service program aims to strengthen the competence of automotive workshop MSMEs in mastering microcontroller-based starter system technology, enabling them to adapt to the era of vehicle digitalization. The program was carried out through several stages: identification of training needs, delivery of basic theory on microcontrollers and starter systems, practical sessions in module assembly and programming, followed by mentoring and evaluation. The results of the evaluation showed an 85% increase in participants’ understanding of the digital starter system concept, an 80% improvement in module assembly and programming skills, and a 75% increase in readiness to apply innovative starter systems in workshop services. The novelty of this activity lies in the development of a more applicable digital starter system model tailored to the needs of small-scale workshops. The implementation emphasized a participatory, practice-based approach using learning by doing. Participants, mainly workshop owners and technicians, were guided step by step from component recognition, software operation with Arduino IDE, to the prototyping of functional microcontroller-based starter systems. To ensure sustainability, the program also provided training modules, video tutorials, and online mentoring, allowing participants to continue practicing independently after the training. Beyond improving technical competence, this activity also fostered an innovative mindset among participants, making them more confident to provide modern, technology-oriented services. In the long term, the program is expected to enhance the competitiveness of automotive MSMEs, strengthen customer trust, and build collaborative networks between higher education institutions and local workshops in supporting vocational education and digital transformation.